2002
DOI: 10.1016/s0022-5347(05)64153-5
|View full text |Cite
|
Sign up to set email alerts
|

An Outcome Prediction Model for Patients with Clear Cell Renal Cell Carcinoma Treated with Radical Nephrectomy Based on Tumor Stage, Size, Grade and Necrosis: The Ssign Score

Abstract: In patients with clear cell renal cell carcinoma 1997 TNM stage, tumor size, nuclear grade and histological tumor necrosis were significantly associated with cancer specific survival. We present a scoring system based on these features that can be used to predict outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
583
0
13

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,001 publications
(610 citation statements)
references
References 22 publications
14
583
0
13
Order By: Relevance
“…The associations of B7-H1 and B7-H4 tumor expression with death from any cause, death from RCC, and cancer progression were evaluated by using Cox proportional hazards regression models. Associations with death from RCC were further adjusted for the SSIGN (stage, size, grade, and necrosis) score, a prognostic composite score specifically developed for patients with clear cell RCC (34). These associations were summarized by using risk ratios and 95% C.I.s.…”
Section: B7-h4 Immunohistochemical Stainingmentioning
confidence: 99%
“…The associations of B7-H1 and B7-H4 tumor expression with death from any cause, death from RCC, and cancer progression were evaluated by using Cox proportional hazards regression models. Associations with death from RCC were further adjusted for the SSIGN (stage, size, grade, and necrosis) score, a prognostic composite score specifically developed for patients with clear cell RCC (34). These associations were summarized by using risk ratios and 95% C.I.s.…”
Section: B7-h4 Immunohistochemical Stainingmentioning
confidence: 99%
“…Park et al [15] reported that a cystic change of more than 5% of the tumor is an independent good prognostic factor. However, it is reported that clear cell RCC tumors with cystic necrosis carry a significantly worse prognosis than cRCCs [16]. …”
Section: Discussionmentioning
confidence: 99%
“…FNG is frequently used for RCC prognosis and is a component of many prognostic predictor scores, such as the UCLA Integrated Staging System (UISS) [15] and the Mayo Clinic tumor stage, size, grade and necrosis (SSIGN) score [16,17]. Therefore, it was surprising that MHCI expression was found to be independent of FNG.…”
Section: Discussionmentioning
confidence: 99%